Bone marrow concentrate promotes bone regeneration with a suboptimal-dose of rhBMP-2 - Egashira, Kazuhiro (PLoS One, 2018)
Bone marrow concentrate (BMC), which is enriched in mononuclear cells (MNCs) and platelets, has recently attracted the attention of clinicians as a new optional means for bone engineering. We previously reported that the osteoinductive effect of bone morphogenetic protein-2 (BMP-2) could be enhanced synergistically by co-transplantation of peripheral blood (PB)-derived platelet-rich plasma (PRP). This study aims to investigate whether BMC can effectively promote bone formation induced by low-dose BMP-2, thereby reducing the undesirable side-effects of BMP-2, compared to PRP. Human BMC was obtained from bone marrow aspirates using an automated blood separator. The BMC was then seeded onto β-TCP granules pre-adsorbed with a suboptimal-dose (minimum concentration to induce bone formation at 2 weeks in mice) of recombinant human (rh) BMP-2. These specimens were transplanted subcutaneously to the dorsal skin of immunodeficient-mice and the induction of ectopic bone formation was assessed 2 and 4 weeks post-transplantation. Transplantations of five other groups [PB, PRP, platelet-poor plasma (PPP), bone marrow aspirate (BM), and BM-PPP] were employed as experimental controls. Then, to clarify the effects on vertical bone augmentation, specimens from the six groups were transplanted for on-lay placement on the craniums of mice. The results indicated that BMC, which contained an approximately 2.5-fold increase in the number of MNCs compared to PRP, could accelerate ectopic bone formation until 2 weeks post-transplantation. On the cranium, the BMC group promoted bone augmentation with a suboptimal-dose of rhBMP-2 compared to other groups. Particularly in the BMC specimens harvested at 4 weeks, we observed newly formed bone surrounding the TCP granules at sites far from the calvarial bone. In conclusion, the addition of BMC could reduce the amount of rhBMP-2 by one-half via its synergistic effect on early-phase osteoinduction. We propose here that BMC transplantation facilitates the clinical use of rhBMP-2 as an alternative strategy for bone engineering.